Hot homogenization process optimization for fragrance encapsulation in solid lipid nanoparticles. (14th July 2015) - Cortial, Angèle; Vocanson, Marc; Loubry, Estelle; Briançon, Stéphanie
Abstract Solid lipid nanoparticles (SLNs) loaded with perfume were prepared using a hot homogenization process coupled with ultrasounds. The objective was to develop a simple process adjustable to several kinds of lipids. The process comprised two steps: a pre‐emulsion of the melted lipids in water followed by a size reduction by sonication, before cooling. The study of several formulation parameters showed that the size distribution of SLNs depended essentially on the sonication step, and especially on the ultrasounds power and time. Five types of SLNs loaded with perfume were produced, based on petrolatum, candelilla, shea butter, C10‐18 triglycerides, and cetyl palmitate. The size distribution was below 200 nm with a narrow size distribution. Moreover, high encapsulation efficiency was obtained, at least 66.5% (±0.5) for petrolatum SLNs and 94.9% (±0.5) for cetyl palmitate SLNs and the loading % was comprised between 4.9% (±0.5) (petrolatum) and 7.0% (±0.5) (cetyl palmitate). A correlation between the partition coefficient of the molecules and the encapsulation efficiency was established for all lipids except cetyl palmitate. Cetyl palmitate, candelilla and petrolatum SLNs were stable for at least one month at 4 °C and 25 °C. Copyright © 2015 John Wiley & Sons, Ltd.